I presume that your second "if" should really be read as "what is." Just substitute each number where the symbols appear in f(x):
f(3/2) = 3/2 + (7/2)(3/2) = 3/2(9/2) = 27/4 or 6 3/4 or 6.75.
(You should be able to do each separate operation in your head; a calculator is not needed.)
Live long and prosper.
2007-01-27 06:24:18
·
answer #1
·
answered by Dr Spock 6
·
1⤊
0⤋
First: the problem gives you the value for "a" > replace "7/2" with the a-variable in the function...
Æ(x) = x + (7/2)x
Sec: replace "3/2" with the x-variables in the function...
Æ(3/2) = 3/2 + (7/2)(3/2)
= 3/2 + (7*3)/(2*2
= 3/2 + 21/4 > use your calculator
= 27/4
2007-01-27 14:26:53
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
Just plug in numbers for a and x:
f(3/2)=3/2+(7/2*3/2)
f(3/2)=3/2+21/4
f(3/2)=6/4+21/4
f(3/2)=27/4 or 6 3/4
I hope this helps!
2007-01-27 15:49:17
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
f(x) = x + ax
a = 7/2 if f(3/2)
Then, by definition of f(x),
f(3/2) = (3/2) + a(3/2)
But a = 7/2, so
f(3/2) = (3/2) + (7/2)(3/2)
f(3/2) = (3/2) + (21/4)
f(3/2) = (6/4) + (21/4) = 27/4
2007-01-27 14:28:09
·
answer #4
·
answered by Puggy 7
·
1⤊
0⤋
what are u trying to ask? But i think i have an idea.
2007-01-27 14:27:29
·
answer #5
·
answered by memo 2
·
1⤊
0⤋